Security and Safety in the Glyphosate Debate: A Chemical Cocktail for Discussion - Silva Garzon, Diego (Alternautas, 2022)
The WHO’s International Agency for Research on Cancer (IARC) released on the 20th of March 2015 in Lyon (France) a controversial report stating that glyphosate, the world’s most widely used herbicide, is probably carcinogenic for humans. The use of the word “probably” is meant to clarify that although there is a positive correlation between exposure to the chemical agent and cancer, other explanations (such as chance, bias, or confounding) could not be fully ruled out (International Agency for Research on Cancer 2015). While the debate triggered by this report has revolved around the agricultural uses of glyphosate at the international level, in Colombia the debate has been associated with the use of glyphosate to eliminate one of the main financial sources of insurgent groups: cocaine crops. Moreover, while the use of glyphosate in Colombia was banned for the eradication of illegal crops shortly after the release of the WHO report, its use remains unproblematic as a strategy of crop management for legal agricultural crops. How can these different responses to the evidence presented in the WHO report on glyphosate be explained?